Analysis of regional features of the tibial plateau fractures in the Rostov region - George S. Golube; Stanislav G. Andrienko; Roman A. Khadi (Travmatologiâ i Ortopediâ Rossii, 2023)
Background. The prevalence of tibial plateau fractures reaches 51.7 per 100,000 population per year, accounting for approximately 1% of all fractures, and is associated with the development of post-traumatic knee osteoarthritis in 25-45% of cases.